A scratch-resistant soft-touch ABS composite material and preparation method thereof

By introducing nanoclay masterbatches, SAS copolymers and SMMA into ABS composite materials, and using the surfactivity transformation technology of liquid polysiloxane, the problem of insufficient scratch resistance of soft-tactile ABS materials in the prior art is solved, and high scratch resistance and good soft-tactile sensation are achieved.

CN119752093APending Publication Date: 2025-04-04SHANGHAI SUNNY NEW TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411981077.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing soft-touch ABS composite materials are difficult to maintain a good soft-touch while improving scratch resistance, which limits its use range.

Method used

By introducing nanoclay masterbatches, SAS copolymers and amorphous polymer SMMA into the ABS composite, combined with the surfactant modification technology of liquid polysiloxanes, a scratch-resistant layer is formed and a soft touch is maintained.

Benefits of technology

It achieves the scratch resistance of ABS composite materials significantly improves the basis of maintaining soft touch, and extends the service time of the components.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and relates to a scratch-resistant soft-touch ABS composite material and a preparation method thereof. The scratch-resistant soft-touch ABS composite material contains 100 parts of ABS, 15-40 parts of toughening agent, 10-35 parts of SAS, and 5-20 parts of nanoclay masterbatch by weight; the nanoclay masterbatch contains nanoclay, liquid polysiloxane, ABS, and SMMA, and the preparation process of the nanoclay masterbatch is: first, nanoclay and liquid polysiloxane are mixed in a high mixer at 30-60°C for 5-8 minutes to obtain surface-treated nanoclay, and then the surface-treated nanoclay is melt-blended with other components and then extruded and granulated to obtain the nanoclay masterbatch; the preparation method is to melt-blend each component in proportion and then extrude and granulate. The present invention successfully solves the technical problem that the soft-touch ABS composite material is difficult to maintain its good soft touch when improving the scratch resistance, and provides the possibility for the application of ABS composite materials in more fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a scratch-resistant soft-touch ABS composite material and a preparation method thereof. Background Art

[0002] Acrylonitrile-butadiene-styrene (ABS) is a thermoplastic engineering plastic. It is widely used in automotive interiors, home appliance housings, luggage, toys and other fields due to its good processability, excellent appearance characteristics, low creep, excellent dimensional stability and high impact strength, as well as its non-toxicity, odorlessness and low water absorption. With the rise of young consumer groups, consumer demand has changed significantly, from preferring high-gloss beautiful appearance to pursuing matte skin-friendly texture. Soft-touch materials that can bring emotional comfort after long-term contact have become increasingly popular among consumers in recent years.

[0003] However, the unsaturated double bonds in the ABS molecular chain react under the influence of external conditions such as light, heat and oxygen, causing the material to turn yellow and its mechanical properties to deteriorate, thus affecting its scratch resistance and making ABS more susceptible to scratches in daily use. In addition, under the influence of external factors such as external force and friction, the soft-touch surface is also prone to scratches, which in turn affects its appearance and limits its scope of use.

[0004] Patent application CN118562243A discloses a soft ABS composition with good appearance, its preparation method and application. The patent selects a styrene-acrylonitrile copolymer with a specific acrylonitrile content of 17-24.5wt%, adds a styrene elastomer, and supplements with a styrene oligomer with a number average molecular weight of not more than 3000 as a flow modifier, so that the ABS composition has lower hardness and better appearance. However, the scratch resistance of the soft-touch ABS material still needs to be improved.

[0005] Patent application CN105131870A discloses a scratch-resistant high-gloss ABS composite material and a preparation method thereof. The composite material improves the hardness and glossiness of the material by adding polycarbonate resin to ABS resin, and further enhances the scratch resistance of the material by adding a scratch-resistant agent. The composite material has good scratch resistance, high gloss and excellent mechanical properties, and can be widely used in fields such as electronic appliances and automotive interiors that have high requirements for appearance and scratch resistance. However, the material is relatively hard and lacks a soft touch, which also limits its scope of use.

[0006] In summary, how to improve the scratch resistance of soft-touch ABS composite materials while maintaining their good soft touch is still a problem that needs to be solved. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a scratch-resistant soft-touch ABS composite material and a preparation method thereof.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A scratch-resistant soft-touch ABS composite material, comprising, by weight, 100 parts of ABS, 15-40 parts of a toughening agent, 10-35 parts of SAS (styrene-acrylonitrile-silicone copolymer), and 5-20 parts of a nano-clay masterbatch;

[0010] The toughening agent is one or more of methyl methacrylate-butadiene-styrene terpolymer (MBS), ABS high rubber powder, hydrogenated styrene-butadiene-styrene block copolymer (SEBS) and styrene-butadiene rubber;

[0011] The nanoclay masterbatch contains nanoclay, liquid polysiloxane, ABS, and SMMA (styrene dimethyl methacrylate copolymer). The preparation process of the nanoclay masterbatch is as follows: firstly, the nanoclay and the liquid polysiloxane are mixed in a high-speed mixer at 30-60° C. for 5-8 minutes to obtain the surface-treated nanoclay, and then the surface-treated nanoclay is melt-blended with other components and then extruded and granulated (i.e., firstly, the premix is ​​mixed evenly in a high-speed mixer at a speed of 200-400 rpm to form a premix, and then the premix is ​​added from the main feeding port and granulated in a twin-screw extruder), so as to obtain the nanoclay masterbatch;

[0012] The nanoclay is one or more of montmorillonite nanoclay, kaolin nanoclay and attapulgite nanoclay.

[0013] As the preferred technical solution:

[0014] The scratch-resistant soft-touch ABS composite material as described above has a melt index of 5-45 g / 10 min at 220° C. and 10 kg.

[0015] In the scratch-resistant soft-touch ABS composite material as described above, the liquid polysiloxane is ternary copolymer block silicone oil and / or polydimethyl silicone oil.

[0016] In the scratch-resistant soft-touch ABS composite material as described above, the melt index of SMMA at 230° C. and 3.8 kg is 8-20 g / 10 min.

[0017] In the scratch-resistant soft-touch ABS composite material as described above, the nanoclay masterbatch contains 5-15 parts of nanoclay, 1-3 parts of liquid polysiloxane, 100 parts of ABS, and 10-40 parts of SMMA, by weight.

[0018] A scratch-resistant soft-touch ABS composite material as described above, wherein the nanoclay masterbatch further contains, by weight, 2-5 parts of a compatibilizer, 0.2-0.5 parts of an antioxidant b, and 1-3 parts of a dispersant b;

[0019] The compatibilizer is one or more of ethylene-acrylate-glycidyl methacrylate terpolymer, ABS-g-GMA, SAN-g-MAH and SEBS-g-MAH;

[0020] Antioxidant b is a mixture of a primary antioxidant and an auxiliary antioxidant in a mass ratio of 1:1, the primary antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate]pentaerythritol ester (1010) and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl ester (1076), and the auxiliary antioxidant is one or more of (2,4-di-tert-butylphenyl) phosphite triester (168) and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite (626);

[0021] The dispersant b is one or more of ethylene-propylene copolymer wax (A-C540A) and oxidized polyethylene wax (A-C639A).

[0022] The scratch-resistant soft-touch ABS composite material as described above, wherein the scratch-resistant soft-touch ABS composite material further comprises, by weight, 0.3-0.6 parts of antioxidant a, 0.6-1 parts of weathering agent, and 0.5-1 parts of dispersant a;

[0023] Antioxidant a is a mixture of a primary antioxidant and an auxiliary antioxidant in a mass ratio of 1:1, the primary antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate]pentaerythritol ester (1010) and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl ester (1076), and the auxiliary antioxidant is one or more of (2,4-di-tert-butylphenyl) phosphite triester (168) and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite (626);

[0024] The weathering agent is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (UV770), 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole (UVP) and 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (UV234);

[0025] The dispersant a is one or more of pentaerythritol stearate (PETS) and ethylene bisstearamide (EBS).

[0026] The scratch-resistant soft-touch ABS composite material as described above has a color difference ΔE≤1.6, a Shore D hardness≤49, and a glossiness of ≤28.

[0027] The present invention also provides a method for preparing a scratch-resistant soft-touch ABS composite material as described in any of the above items, wherein the components are melt-blended in proportion and then extruded and granulated (i.e., first mixed evenly in a high-speed mixer at a speed of 220-480 rpm to form a premix, and then the formed premix is ​​added from the main feeding port and granulated in a twin-screw extruder) to obtain a scratch-resistant soft-touch ABS composite material.

[0028] The principle of the present invention is as follows:

[0029] The present invention focuses on the optimization of the scratch resistance of ABS composite materials, and the core lies in three-step fine processing. The first step is to use liquid polysiloxane containing -Si-O- groups to implement surface activity modification on nanoclay (the polar groups of liquid polysiloxane react with the surface polar groups of nanoclay), which is like "pre-treating" the nanoclay to give it better reactivity. Then, in conjunction with the shear force of the twin-screw extruder, the intercalation structure of the nanoclay is strongly propped open to achieve its uniform and efficient dispersion in ABS, laying a solid microstructural foundation for subsequent composites. The second step is to introduce the amorphous polymer SMMA, and with the help of its amorphous polar groups, "chemically connect" with the pretreated nanoclay, greatly improve the compatibility and dispersion stability of nanoclay in ABS. The two work together, and the nanoclay plays an interlocking and bridging role, like weaving an anti-crack net inside the material, curbing crack growth and reducing the generation of silver streaks. In addition, the high hardness advantage of SMMA itself synergistically improves the scratch resistance of ABS composite materials. The third step is to compound SAS and use its silicone structural characteristics to generate a scratch-resistant layer "in situ" on the surface of the composite material. Thanks to the high relative molecular weight of SAS, it eliminates migration, stickiness, and slippery problems, completely retains the soft touch, and effectively extends the service life of the components.

[0030] The prior art usually improves the scratch resistance of the composite material by adding a high-hardness scratch-resistant agent such as PMMA (polymethyl methacrylate), but this will sacrifice the soft touch of ABS. The reason is that the surface hardness of PMMA is extremely high, and in order to prepare an ABS composite material with scratch resistance, a higher content of PMMA needs to be added. When the ABS / PMMA composite material is sheared, dispersed and distributed by a twin-screw extruder, PMMA will be evenly distributed on the surface of ABS, thereby enhancing the surface hardness and gloss of the ABS material. Although this improves the scratch resistance of ABS, it also reduces its soft touch. The present invention uses the "bridge" effect of SAS to improve the scratch resistance while maintaining the soft touch of ABS. Specifically, the present invention first uses SMMA and nanoclay to prepare a masterbatch to improve the tear resistance and scratch resistance of the material, and then uses the silicone structure characteristics of SAS to generate a scratch-resistant layer on the surface of the composite material. Since the surface hardness of SAS is much lower than that of PMMA, the prepared soft-touch ABS composite material has good scratch resistance while avoiding the reduction of soft touch.

[0031] Beneficial effects:

[0032] The present invention successfully solves the technical problem that it is difficult for soft-touch ABS composite materials to maintain their good soft touch while improving their scratch resistance, thus providing the possibility for the application of ABS composite materials in more fields. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0035] Color difference △E: refer to GMW 14688-2018 standard, use a colorimeter to perform a five-finger scratch test on the sample to be tested, use a 1mm metal scraper to scratch two sets of parallel scratches perpendicular to each other on the surface of the sample to be tested with a force of 5-15N, and measure the color difference of the scratched area before and after scratching.

[0036] Shore D hardness: Tested in accordance with GB / T 2411-2008 standard.

[0037] Gloss: Refer to GB / T 8807-1988 standard, use 60° incident light, measure the intensity ratio of regular reflected light and diffuse reflected light, and get the gloss.

[0038] Example 1

[0039] A method for preparing a scratch-resistant soft-touch ABS composite material, the specific steps are as follows:

[0040] (1) Preparation of raw materials;

[0041] Nanoclay: Montmorillonite nanoclay, the manufacturer is Aumco Group, the brand is NANOLIN

[0042] Liquid polysiloxane: ternary copolymer block silicone oil, the manufacturer is Maitu High-Tech Materials Group Co., Ltd., the brand is MT80;

[0043] ABS: The manufacturer is LG Chemical Company, the brand is LG ABS HI121H, the melt index at 220℃ and 10kg is 22g / 10min;

[0044] SMMA: The manufacturer is LG Chemical Company, the brand is HX500, and the melt index at 230℃ and 3.8kg is 8g / 10min;

[0045] Compatibilizer: ethylene-acrylate-glycidyl methacrylate terpolymer, manufactured by Arkema, brand name AX8900;

[0046] Antioxidant a and antioxidant b: both are mixtures of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;

[0047] Dispersant b: A-C540A, manufactured by Honeywell;

[0048] Toughening agent: MBS, manufactured by Zhongyuan Company, brand name MBS 701;

[0049] SAS: The manufacturer is Dakeneng Yulingtong Co., Ltd., and the brand number is SAS S351;

[0050] Weathering agent: UV770;

[0051] Dispersant a: PETS;

[0052] (2) preparing nanoclay masterbatch;

[0053] First, nano clay and liquid polysiloxane are mixed in a high mixer at 30° C. for 8 minutes to obtain surface-treated nano clay, and then the surface-treated nano clay, ABS, SMMA, a compatibilizer, an antioxidant b and a dispersant b are uniformly mixed in a high mixer at a speed of 400 rpm to form a premix, and then the formed premix is ​​added from a main feeding port, and granulated in a twin-screw extruder to obtain a nano clay masterbatch; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 120° C., 160° C., 200° C., 200° C., 200° C., 200° C., 200° C., 200° C., 200° C., 200° C., 200° C., 200° C.;

[0054] The nanoclay masterbatch is composed of 5 parts of nanoclay, 1 part of liquid polysiloxane, 100 parts of ABS, 10 parts of SMMA, 2 parts of compatibilizer, 0.2 parts of antioxidant b and 1 part of dispersant b by weight;

[0055] (3) ABS, toughening agent, SAS, nanoclay masterbatch, antioxidant a, weathering agent and dispersant a are first mixed uniformly in a high-speed mixer at a speed of 220 rpm to form a premix, and then the formed premix is ​​added from a main feeding port and granulated in a twin-screw extruder to obtain a scratch-resistant soft-touch ABS composite material; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 120° C., 160° C., 200° C., 210° C., 210° C., 210° C., 210° C., 210° C., 200° C., respectively.

[0056] The final scratch-resistant soft-touch ABS composite material is composed of 100 parts of ABS, 15 parts of toughening agent, 35 parts of SAS, 5 parts of nanoclay masterbatch, 0.3 parts of antioxidant a, 0.6 parts of weathering agent and 0.5 parts of dispersant a; the color difference △E of the scratch-resistant soft-touch ABS composite material is 1.6, the Shore D hardness is 49, and the glossiness is 28.

[0057] Comparative Example 1

[0058] A method for preparing an ABS composite material, which is different from Example 1 only in that the nanoclay (montmorillonite nanoclay) is replaced by barium sulfate (manufacturer: Yunfu Hongzhi New Materials Co., Ltd., brand: F-100).

[0059] The color difference ΔE of the finally prepared ABS composite material is 4.7, and the Shore D hardness is 62.

[0060] Compared with Example 1, the color difference ΔE and Shore D hardness of the ABS composite material in Comparative Example 1 are significantly increased. This is because the barium sulfate used in Comparative Example 1 does not have the interlocking and bridging performance in ABS, and cannot inhibit the growth of cracks in ABS and reduce the generation of silver streaks, resulting in an increase in the color difference ΔE; at the same time, the barium sulfate used in Comparative Example 1 is spherical and has a high Mohs hardness, which will greatly increase the surface hardness of the ABS material, resulting in an increase in the Shore D hardness.

[0061] Example 2

[0062] A method for preparing a scratch-resistant soft-touch ABS composite material, the specific steps are as follows:

[0063] (1) Preparation of raw materials;

[0064] Nanoclay: kaolin nanoclay, the manufacturer is Zaozhuang Sanxing High-tech Materials Co., Ltd., brand NK80;

[0065] Liquid polysiloxane: ternary copolymer block silicone oil, the manufacturer is Maitu High-Tech Materials Group Co., Ltd., the brand is MT80;

[0066] ABS: The manufacturer is Sinopec Shanghai Gaoqiao Petrochemical Co., Ltd., the brand is ABS 8391, and the melt index at 220℃ and 10kg is 19g / 10min;

[0067] SMMA: The manufacturer is LG Chemical Company, the brand is HX500, and the melt index at 230℃ and 3.8kg is 8g / 10min;

[0068] Compatibilizer: ABS-g-GMA, the manufacturer is Ningbo Nengzhiguang New Materials Technology Co., Ltd., the brand is E626;

[0069] Antioxidant a and antioxidant b: both are mixtures of antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1;

[0070] Dispersant b: A-C540A, manufactured by Honeywell;

[0071] Toughening agent: ABS high-rubber powder, the manufacturer is Korea Kumho Petrochemical Co., Ltd., brand HR181;

[0072] SAS: The manufacturer is Dakeneng Yulingtong Co., Ltd., and the brand number is SAS S351;

[0073] Weathering agent: UV770;

[0074] Dispersant a: PETS;

[0075] (2) preparing nanoclay masterbatch;

[0076] First, nano clay and liquid polysiloxane are mixed in a high mixer at 45° C. for 7 minutes to obtain surface-treated nano clay, and then the surface-treated nano clay, ABS, SMMA, a compatibilizer, an antioxidant b and a dispersant b are uniformly mixed in a high mixer at a speed of 380 revolutions / min to form a premix, and then the formed premix is ​​added from a main feeding port, and granulated in a twin-screw extruder to obtain a nano clay masterbatch; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 160° C., 200° C., 240° C., 240° C., 240° C., 240° C., 240° C., 240° C., 230° C., respectively;

[0077] The nanoclay masterbatch is composed of 15 parts of nanoclay, 3 parts of liquid polysiloxane, 100 parts of ABS, 40 parts of SMMA, 5 parts of compatibilizer, 0.3 parts of antioxidant b and 3 parts of dispersant b by weight;

[0078] (3) ABS, toughening agent, SAS, nanoclay masterbatch, antioxidant a, weathering agent and dispersant a are first mixed uniformly in a high-speed mixer at a speed of 260 rpm to form a premix, and then the formed premix is ​​added from a main feeding port and granulated in a twin-screw extruder to obtain a scratch-resistant soft-touch ABS composite material; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 160° C., 210° C., 230° C., 240° C., 240° C., 240° C., 240° C., 240° C., 230° C., respectively.

[0079] The final scratch-resistant soft-touch ABS composite material is composed of 100 parts of ABS, 40 parts of toughening agent, 10 parts of SAS, 20 parts of nanoclay masterbatch, 0.6 parts of antioxidant a, 1 part of weathering agent and 1 part of dispersant a; the color difference △E of the scratch-resistant soft-touch ABS composite material is 1, the Shore D hardness is 42, and the glossiness is 15.

[0080] Comparative Example 2

[0081] A method for preparing an ABS composite material, which is different from Example 2 only in that the toughening agent (MBS) is replaced by an acrylic toughening agent (manufacturer: Mitsubishi Chemical Corporation, brand: S2001).

[0082] The color difference ΔE of the finally prepared ABS composite material is 2.6, and the Shore D hardness is 58.

[0083] Compared with Example 2, the color difference ΔE and Shore D hardness of the ABS composite material in Comparative Example 2 are significantly increased. This is because the acrylic toughening agent used in Comparative Example 2 has poor compatibility, and relatively more silver streaks are generated during the scratch resistance test, and the appearance is whitish, thereby increasing the color difference ΔE; at the same time, the toughening effect of the acrylic toughening agent is not good, resulting in an increase in the Shore D hardness of the ABS composite material.

[0084] Example 3

[0085] A method for preparing a scratch-resistant soft-touch ABS composite material, the specific steps are as follows:

[0086] (1) Preparation of raw materials;

[0087] Nanoclay: attapulgite nanoclay, the manufacturer is Anhui Mingmei Mineral Chemical Co., Ltd., brand name PalyGel 200;

[0088] Liquid polysiloxane: a mixture of ternary copolymer block silicone oil (manufacturer: Momentive High-Tech Materials Group Co., Ltd., brand name: MT80) and polydimethylsilicone oil (manufacturer: The Dow Chemical Company, brand name: PMX-200) in a mass ratio of 1:1;

[0089] ABS: The manufacturer is Zhenjiang Chimei Chemical Co., Ltd., the brand is Zhenjiang Chimei ABS PA-757K, the melt index at 220℃ and 10kg is 18g / 10min;

[0090] SMMA: The manufacturer is LG Chemical Company, the brand is HX500, and the melt index at 230℃ and 3.8kg is 8g / 10min;

[0091] Compatibilizer: SAN-g-MAH, manufacturer is Jiayirong Polymer (Shanghai) Co., Ltd., brand name is SAM-010;

[0092] Antioxidant a and antioxidant b: both are mixtures of antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1;

[0093] Dispersant b: A-C639A, manufactured by Honeywell;

[0094] Toughening agent: SEBS, the manufacturer is Shanghai Huaxin International Group Yueyang Petrochemical Co., Ltd., the brand is SEBS YH-501T;

[0095] SAS: The manufacturer is Dakeneng Yulingtong Co., Ltd., and the brand number is SAS S351;

[0096] Weathering agent: UVP;

[0097] Dispersant a: PETS;

[0098] (2) preparing nanoclay masterbatch;

[0099] First, nano clay and liquid polysiloxane are mixed in a high mixer at 50° C. for 6 minutes to obtain surface-treated nano clay, and then the surface-treated nano clay, ABS, SMMA, a compatibilizer, an antioxidant b and a dispersant b are uniformly mixed in a high mixer at a speed of 320 rpm to form a premix, and then the formed premix is ​​added from a main feeding port, and granulated in a twin-screw extruder to obtain a nano clay masterbatch; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 130° C., 170° C., 220° C., 220° C., 230° C., 230° C., 230° C., 230° C., 220° C., respectively;

[0100] The nanoclay masterbatch is composed of 8 parts of nanoclay, 2 parts of liquid polysiloxane, 100 parts of ABS, 25 parts of SMMA, 3 parts of compatibilizer, 0.4 parts of antioxidant b and 1.5 parts of dispersant b by weight;

[0101] (3) ABS, toughening agent, SAS, nanoclay masterbatch, antioxidant a, weathering agent and dispersant a are first mixed uniformly in a high-speed mixer at a speed of 320 rpm to form a premix, and then the formed premix is ​​added from a main feeding port and granulated in a twin-screw extruder to obtain a scratch-resistant soft-touch ABS composite material; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 150° C., 180° C., 220° C., 230° C., 230° C., 230° C., 230° C., 230° C., 220° C., respectively.

[0102] The final scratch-resistant soft-touch ABS composite material is composed of 100 parts of ABS, 25 parts of toughening agent, 20 parts of SAS, 16 parts of nanoclay masterbatch, 0.4 parts of antioxidant a, 0.8 parts of weathering agent and 0.7 parts of dispersant a; the color difference △E of the scratch-resistant soft-touch ABS composite material is 1.1, the Shore D hardness is 43, and the glossiness is 18.

[0103] Comparative Example 3

[0104] A method for preparing an ABS composite material, which is different from Example 3 only in that SAS is replaced by SAN (manufacturer: Zhenjiang Chimei Chemical Co., Ltd., brand: PN-127L150FG).

[0105] The color difference ΔE of the finally prepared ABS composite material is 3.9, and the Shore D hardness is 56.

[0106] Compared with Example 3, the color difference ΔE and Shore D hardness of the ABS composite material in Comparative Example 3 are significantly increased. This is because the SAN used in Comparative Example 3 lacks siloxy groups and cannot effectively bond with the nanoclay masterbatch, making it difficult for the nanoclay masterbatch to be better dispersed in the ABS composite material. When subjected to external scratches, it cannot effectively resist scratches, is prone to surface damage, is prone to silver streaks, and has poor scratch resistance, resulting in an increase in the color difference ΔE. At the same time, the surface hardness of SAN itself is relatively high, resulting in an increase in the Shore D hardness of the material.

[0107] Example 4

[0108] A method for preparing a scratch-resistant soft-touch ABS composite material, the specific steps are as follows:

[0109] (1) Preparation of raw materials;

[0110] Nanoclay: Montmorillonite nanoclay, the manufacturer is Aumco Group, the brand is NANOLIN

[0111] Liquid polysiloxane: polydimethylsilicone, manufactured by Dow Chemical Company, brand name PMX-200;

[0112] ABS: The manufacturer is LG Chemical Company, the brand is LG ABS HP181 NP, the melt index at 220℃ and 10kg is 42g / 10min;

[0113] SMMA: manufacturer is INEOS Styrolution, brand number is 90, melt index is 16g / 10min at 230℃ and 3.8kg;

[0114] Compatibilizer: SEBS-g-MAH, manufacturer is Kraton, brand name is FG1901 GT;

[0115] Antioxidant a and antioxidant b: both are mixtures of antioxidant 1076 and antioxidant 626 in a mass ratio of 1:1;

[0116] Dispersant b: A-C639A, manufactured by Honeywell;

[0117] Toughening agent: styrene butadiene rubber, the manufacturer is China Petroleum Lanzhou Petrochemical Company, the brand is SBR 1778E;

[0118] SAS: The manufacturer is Dakeneng Yulingtong Co., Ltd., and the brand number is SAS TW21H;

[0119] Weathering agent: UV234;

[0120] Dispersant a: EBS;

[0121] (2) preparing nanoclay masterbatch;

[0122] First, nano clay and liquid polysiloxane are mixed in a high mixer at 60° C. for 6 minutes to obtain surface-treated nano clay, and then the surface-treated nano clay, ABS, SMMA, a compatibilizer, an antioxidant b and a dispersant b are uniformly mixed in a high mixer at a speed of 260 rpm to form a premix, and then the formed premix is ​​added from a main feeding port, and granulated in a twin-screw extruder to obtain a nano clay masterbatch; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 140° C., 180° C., 210° C., 210° C., 210° C., 210° C., 210° C., 210° C., 200° C., respectively;

[0123] The nanoclay masterbatch is composed of 12 parts of nanoclay, 2 parts of liquid polysiloxane, 100 parts of ABS, 30 parts of SMMA, 4 parts of compatibilizer, 0.5 parts of antioxidant b and 2.5 parts of dispersant b by weight;

[0124] (3) ABS, toughening agent, SAS, nanoclay masterbatch, antioxidant a, weathering agent and dispersant a are first mixed uniformly in a high-speed mixer at a speed of 400 rpm to form a premix, and then the formed premix is ​​added from a main feeding port and granulated in a twin-screw extruder to obtain a scratch-resistant soft-touch ABS composite material; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 130° C., 180° C., 210° C., 210° C., 210° C., 210° C., 210° C., 210° C., 200° C., respectively.

[0125] The final scratch-resistant soft-touch ABS composite material is composed of 100 parts of ABS, 30 parts of toughening agent, 25 parts of SAS, 8 parts of nanoclay masterbatch, 0.5 parts of antioxidant a, 0.6 parts of weathering agent and 1 part of dispersant a; the color difference △E of the scratch-resistant soft-touch ABS composite material is 1.5, the Shore D hardness is 48, and the glossiness is 22.

[0126] Comparative Example 4

[0127] A method for preparing an ABS composite material, which is different from Example 4 only in that SMMA is replaced by PMMA (manufacturer: Zhenjiang Chimei Chemical Co., Ltd., brand: CM211).

[0128] The color difference ΔE of the finally prepared ABS composite material is 2.8, and the Shore D hardness is 64.

[0129] Compared with Example 4, the color difference ΔE and Shore D hardness of the ABS composite material in Comparative Example 4 are significantly increased. This is because the PMMA used in Comparative Example 4 cannot form an effective chemical connection with the nanoclay, and the compatibility and dispersion stability of the nanoclay in ABS are deteriorated. When subjected to external scratches, cracks are more likely to occur and expand, thereby increasing the color difference; at the same time, due to the high surface hardness of PMMA, the Shore D hardness is increased after the ABS composite material is prepared.

[0130] Example 5

[0131] A method for preparing a scratch-resistant soft-touch ABS composite material, the specific steps are as follows:

[0132] (1) Preparation of raw materials;

[0133] Nanoclay: kaolin nanoclay, the manufacturer is Zaozhuang Sanxing High-tech Materials Co., Ltd., brand NK80;

[0134] Liquid polysiloxane: polydimethylsilicone, manufactured by Dow Chemical Company, brand name PMX-200;

[0135] ABS: The manufacturer is Sinopec Shanghai Gaoqiao Petrochemical Co., Ltd., the brand is ABS 3504, and the melt index at 220℃ and 10kg is 5.2g / 10min;

[0136] SMMA: manufacturer is INEOS Styrolution, brand number is 90, melt index is 16g / 10min at 230℃ and 3.8kg;

[0137] Compatibilizer: SEBS-g-MAH, manufacturer is Kraton, brand name is FG1901 GT;

[0138] Antioxidant a and antioxidant b: both are mixtures of antioxidant 1076 and antioxidant 626 in a mass ratio of 1:1;

[0139] Dispersant b: a mixture of A-C540A and A-C639A in a mass ratio of 1:1, and both A-C540A and A-C639A are from Honeywell;

[0140] Toughening agent: a mixture of MBS (manufacturer: Zhongyuan Company, brand name: MBS 724) and SEBS (manufacturer: Kraton Company, brand name: SEBS G1650) in a mass ratio of 1:1;

[0141] SAS: The manufacturer is Dakeneng Yulingtong Co., Ltd., and the brand number is SAS TW21H;

[0142] Weathering agent: UVP;

[0143] Dispersant a: EBS;

[0144] (2) preparing nanoclay masterbatch;

[0145] First, nano clay and liquid polysiloxane are mixed in a high mixer at 60° C. for 5 minutes to obtain surface-treated nano clay, and then the surface-treated nano clay, ABS, SMMA, a compatibilizer, an antioxidant b and a dispersant b are uniformly mixed in a high mixer at a speed of 200 rpm to form a premix, and then the formed premix is ​​added from a main feeding port, and granulated in a twin-screw extruder to obtain a nano clay masterbatch; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 150° C., 190° C., 230° C., 230° C., 230° C., 230° C., 230° C., 230° C., 210° C.;

[0146] The nanoclay masterbatch is composed of 9 parts of nanoclay, 3 parts of liquid polysiloxane, 100 parts of ABS, 15 parts of SMMA, 3 parts of compatibilizer, 0.3 parts of antioxidant b and 2 parts of dispersant b by weight;

[0147] (3) ABS, toughening agent, SAS, nanoclay masterbatch, antioxidant a, weathering agent and dispersant a are first mixed uniformly in a high-speed mixer at a speed of 480 rpm to form a premix, and then the formed premix is ​​added from a main feeding port and granulated in a twin-screw extruder to obtain a scratch-resistant soft-touch ABS composite material; wherein the setting temperatures of the twin-screw extruder from the first zone to the ninth zone are: 150° C., 200° C., 220° C., 220° C., 220° C., 220° C., 220° C., 220° C., 210° C., respectively.

[0148] The final scratch-resistant soft-touch ABS composite material is composed of 100 parts of ABS, 35 parts of toughening agent, 30 parts of SAS, 10 parts of nanoclay masterbatch, 0.4 parts of antioxidant a, 0.7 parts of weathering agent and 0.8 parts of dispersant a; the color difference △E of the scratch-resistant soft-touch ABS composite material is 1.2, the Shore D hardness is 46, and the glossiness is 24.

[0149] Comparative Example 5

[0150] A method for preparing an ABS composite material, which is different from Example 5 only in that no liquid polysiloxane is added in step (2).

[0151] The color difference ΔE of the final ABS composite material is 2.4, and the Shore D hardness is 53.

[0152] Compared with Example 5 and Comparative Example 4, the color difference ΔE and Shore D hardness of the ABS composite material are significantly increased. This is because no liquid polysiloxane is added to the surface of the nanoclay for surface treatment, the reaction activity of the nanoclay is low, and its intercalation structure is difficult to be effectively opened, resulting in the inability to achieve uniform and efficient dispersion in ABS, and agglomeration is prone to occur. The nanoclay cannot play a good role in inhibiting cracks and reducing the generation of silver streaks. When the material is affected by external factors such as scratches, the color changes greatly and the color difference ΔE increases. At the same time, due to the poor dispersion of the nanoclay, the hardness cannot be adjusted in coordination with SMMA, and the Shore D hardness increases.

Claims

1. A scratch-resistant soft-touch ABS composite material, characterized in that: By weight, it contains 100 parts of ABS, 15-40 parts of toughening agent, 10-35 parts of SAS, and 5-20 parts of nano clay masterbatch; The toughening agent is one or more of methyl methacrylate-butadiene-styrene terpolymer, ABS high-rubber powder, hydrogenated styrene-butadiene-styrene block copolymer and styrene-butadiene rubber; The nanoclay masterbatch contains nanoclay, liquid polysiloxane, ABS, and SMMA. The preparation process of the nanoclay masterbatch is as follows: firstly, the nanoclay and the liquid polysiloxane are mixed in a high-speed mixer at 30-60°C for 5-8 minutes to obtain the surface-treated nanoclay, and then the surface-treated nanoclay is melt-blended with other components and then extruded and granulated to obtain the nanoclay masterbatch; The nanoclay is one or more of montmorillonite nanoclay, kaolin nanoclay and attapulgite nanoclay.

2. The scratch-resistant soft-touch ABS composite material according to claim 1, characterized in that: The melt index of ABS at 220°C and 10kg is 5-45g / 10min.

3. The scratch-resistant soft-touch ABS composite material according to claim 1, characterized in that: The liquid polysiloxane is a ternary copolymer block silicone oil and / or polydimethyl silicone oil.

4. The scratch-resistant soft-touch ABS composite material according to claim 1, characterized in that: The melt index of SMMA at 230°C and 3.8 kg is 8-20 g / 10 min.

5. The scratch-resistant soft-touch ABS composite material according to claim 1, characterized in that: The nanoclay masterbatch contains 5-15 parts of nanoclay, 1-3 parts of liquid polysiloxane, 100 parts of ABS and 10-40 parts of SMMA by weight.

6. The scratch-resistant soft-touch ABS composite material according to claim 5, characterized in that: The nanoclay masterbatch also contains 2-5 parts of a compatibilizer, 0.2-0.5 parts of an antioxidant b, and 1-3 parts of a dispersant b, by weight.

7. The scratch-resistant soft-touch ABS composite material according to claim 1, characterized in that: The scratch-resistant soft-touch ABS composite material also contains 0.3-0.6 parts of antioxidant a, 0.6-1 parts of weathering agent, and 0.5-1 parts of dispersant a by weight.

8. The scratch-resistant soft-touch ABS composite material according to any one of claims 1 to 7, characterized in that: The color difference of the scratch-resistant soft-touch ABS composite material is △E≤1.6, the Shore D hardness is ≤49, and the glossiness is ≤28.

9. A method for preparing a scratch-resistant soft-touch ABS composite material as claimed in any one of claims 1 to 8, characterized in that: The components are melt-blended in proportion and then extruded and granulated to obtain a scratch-resistant soft-touch ABS composite material.

Citation Information

Patent Citations

  • Preparation technology for solvent-type high-viscosity pressure-sensitive adhesive

    CN105131870A

  • Soft ABS (Acrylonitrile Butadiene Styrene) composition with good appearance as well as preparation method and application thereof

    CN118562243A